A bvrR/bvrS Non-Polar Brucella abortus Mutant Confirms the Role of the Two-Component System BvrR/BvrS in Virulence and Membrane Integrity - Rivas-Solano, Olga (2023)
Brucella abortus is a bacterial pathogen causing bovine brucellosis worldwide. This facultative extracellular–intracellular pathogen can be transmitted to humans, leading to a zoonotic disease. The disease remains a public health concern, particularly in regions where livestock farming is present. The two-component regulatory system BvrR/BvrS was described by isolating the attenuated transposition mutants bvrR::Tn5 and bvrS::Tn5, whose characterization led to the understanding of the role of the system in bacterial survival. However, a phenotypic comparison with deletion mutants has not been performed because their construction has been unsuccessful in brucellae and difficult in phylogenetically related Rhizobiales with BvrR/BvrS orthologs. Here, we used an unmarked gene excision strategy to generate a B. abortus mutant strain lacking both genes, called B. abortus ∆bvrRS. The deletion was verified through PCR, Southern blot, Western blot, Sanger sequencing, and whole-genome sequencing, confirming a clean mutation without further alterations at the genome level. B. abortus ∆bvrRS shared attenuated phenotypic traits with both transposition mutants, confirming the role of BvrR/BvrS in pathogenesis and membrane integrity. This B. abortus ∆bvrRS with a non-antimicrobial marker is an excellent tool for continuing studies on the role of BvrR/BvrS in the B. abortus lifestyle.